Meta Analisis: Efektivitas Model Circ dalam Meningkatkan Keterampilan Menulis Siswa Sekolah Dasar - Amelia, Fatia Tri Rizki; Sarifah, Iva; Imaningtyas, Imaningtyas (Program Studi Pendidikan Bahasa Program Pascasarjana Universitas Negeri Jakarta, 2024)
This study aims to determine the effectiveness of the CIRC learning model in improving elementary school students' writing skills in learning Indonesia language. This study uses research methods literature review with meta analysis techniques. There were 12 articles published on Google Scholar and Sinta in the 2018-2023 period that were analyzed in this study. Analysis of the data used in this study is a comparison test with paired t-test using the SPSS 22 application. The results obtained were the average score for writing skills before using the CIRC learning model of 53.5 and after using the CIRC learning model of 78.2. The results of calculations using the paired samples test obtained a t-count value of 10.66 with a significant level of